Utilização do resíduo industrial do tomate na alimentação de vacas leiteiras: revisão bibliográfica - Reis, Bianca Cardoso dos [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Notoriously, dairy farming is of paramount importance to the Brazilian economy, however, one of the challenges for greater competitiveness of the activity in the market comes from animal feed, since up to 75% of production costs can be attributed to this aspect. And even so, in times of drought, food supply is limited and increases costs even more. In this context, the use of waste from the food industry can be a viable and economical solution. Among them, tomato waste deserves to be highlighted, since Brazil is the 9th largest producer of the crop in the world and a large part of the production is destined for industrial processing, which generates a large volume of waste. In this review on the use of industrial tomato residues in the feeding of dairy cows, information was used about various sources, including research institutions, specialized websites, national and international magazines, technical bulletins, proceedings of symposia and congresses. , technical circulars, articles published in national and international journals and books. The objective was to compare the results obtained by several studies showing some 52 aspects of the industrial residue of the tomato as an ingredient of rations, its nutritional composition, the use for feeding dairy cows related to the production and quality of milk, in addition to the health of the cow itself. In this context, the use of industrial tomato residue in the feeding of dairy cows is of paramount importance, in view of its versatile and nutritious character. In this work, it is observed that the RIT has great potential in the nutrition of production animals, having the practical indication of inclusion of up to 30% in the ruminant diet, and proves to be the industrial residue with the best cost benefit among those analyzed economically.

Notoriamente, a pecuária leiteira é de suma importância para a economia brasileira, entretanto, um dos desafios para a maior competitividade da atividade no mercado vem da alimentação animal, visto que até 75% dos custos de produção podem ser atribuidos a este aspecto. E mesmo assim, em épocas de estiagem, a oferta alimentar se mostra limitada e aumenta ainda mais os custos. Neste âmbito, o emprego de residuos da industria alimentícia pode ser uma solução viável e ecônomica. Entre eles, o resíduo de tomate merece destaque, visto que o Brasil é o 9º maior produtor mundial da cultura e grande parte da produção é destinada ao processamento industrial, o que gera grande volume de resíduos. Nesta revisão sobre a utilização do resíduo industrial do tomate na alimentação de vacas leiteiras, utilizaram-se informações a cerca das diversas fontes, dentre elas instituições de pesquisas, sites especializados, revistas de divulgação nacionais e internacionais, boletins técnicos, anais de simpósios e congressos, circulares técnicas, artigos publicados em periódicos nacionais e internacionais e livros. Objetivou-se 50 comparar os resultados obtidos por diversos trabalhos mostrando alguns aspectos do resíduo industrial do tomate como ingrediente de rações, sua composição nutricional, a utilização para alimentação de vacas leiteiras relacionada com a produção e qualidade do leite, além da saúde da própria vaca. Nesse contexto, o uso do resíduo industrial do tomate na alimentação de vacas leiteiras é de suma importância, tendo em vista seu caráter versátil e nutritivo. Neste trabalho, é observado que o RIT apresenta grande potencial na nutrição dos animais de produção, tendo o a indicação prática de inclusão de até 30% na dieta de ruminantes, e demonstra ser o resíduo industrial de melhor custo benefício entre os analisados economicamente.
Use of tomato industrial waste in feeding dairy cows: bibliographic review
Keywords: Bovino; Rações; Subprodutos; Nutrição Animal